Preterit Expansion and Perfect Demise in Porteño Spanish and Beyond A Critical Perspective on Cognitive Grammaticalization Theory - Nore Fløgstad, Guro (Brill's Studies in Historical Linguistics, 2016)
In this book, Guro Nore Fløgstad shows how the Preterit category has expanded in Porteño Spanish, and sheds new light on the outcome of the competition between Perfects and Preterits in Romance, and beyond. Readership: All interested in morphology, historical linguistics, the development of Perfects and Preterits in the languages of the world, especially those concerned with Romance languages, as well as anyone concerned with cognitive and usage-based approaches to language change, grammaticalization, and directionality.